2018
DOI: 10.1007/s10620-018-5327-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-Course Antibiotic Treatment Is Not Inferior to a Long-Course One in Acute Cholangitis: A Systematic Review

Abstract: Aims Our aim was to summarize the available literature on the effect of short- versus long-course antibiotic therapy on acute cholangitis. Methods A systematic review was performed according to the PRISMA Statement. We searched three databases for papers discussing the length of ABT in acute cholangitis. Long and short therapy groups were defined based on the most recent guideline available at the time of publication of the articles. Primary outcomes were the rate of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 25 publications
0
18
0
4
Order By: Relevance
“…The combination of biliary drainage by endoscopic retrograde cholangio‐pancreatography (ERCP) and antimicrobial therapy is the cornerstone of treatment of acute cholangitis 2 3 . However, the optimal duration of antimicrobial therapy is unclear, because there is limited research conducted on this matter 4–9 . Consensus‐based recommendations on antimicrobial treatment duration in current (inter)national guidelines therefore vary from 3 days or less up to 10 days 10–13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of biliary drainage by endoscopic retrograde cholangio‐pancreatography (ERCP) and antimicrobial therapy is the cornerstone of treatment of acute cholangitis 2 3 . However, the optimal duration of antimicrobial therapy is unclear, because there is limited research conducted on this matter 4–9 . Consensus‐based recommendations on antimicrobial treatment duration in current (inter)national guidelines therefore vary from 3 days or less up to 10 days 10–13 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 However, the optimal duration of antimicrobial therapy is unclear, because there is limited research conducted on this matter. [4][5][6][7][8][9] Consensus-based recommendations on antimicrobial treatment duration in current (inter) national guidelines therefore vary from 3 days or less up to 10 days. [10][11][12][13] Unnecessary prolonged antimicrobial therapy increases risk of mortality and side-effects, such as diarrhoea and colitis due to Clostridioides difficile infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, validation of the TG07 remains poor outside Japan [7, 8]. The Charcot triad is traditionally considered diagnostic for AC; however, it has a low sensitivity [13, 14]. In addition to the Charcot triad, TG07 diagnostic criteria include a history of biliary disease, and it has an increased diagnostic sensitivity for the diagnosis of AC [4, 15].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that provided there was source control, a shorter course of less than a week did not result in higher mortality, duration of fever or higher rates of recurrence. (60) Guidelines from the Surgical Infection Society (SIS) (2017) and the IDSA (2010) advocate < 7 days of therapy for patients with source control. (57,61) Tokyo Guidelines for management of acute cholangitis recommend drainage or source control as the mainstay of therapy followed by 4-7 days of appropriate targeted antimicrobial therapy.…”
Section: Intra-abdominal Infectionsmentioning
confidence: 99%